Don't worry darling [videorecording (DVD)] - Wilde, Olivia; Van Dyke, Carey, 1976-; Van Dyke, Shane, 1979-; Silberman, Katie; Pugh, Florence, 1996-; Styles, Harry, 1994-; Berlant, Kate, 1987-; Chan, Gemma, 1982-; Layne, KiKi; Chandler, Sydney; Kroll, Nick; Pine, Chris, 1980- (Warner Bros. Entertainment, Inc., 2022)
A 1950s housewife living with her husband in an idealistic experimental community begins to worry that his glamorous company may be hiding troubling secrets.